Nuclear factor (erythroid‐derived 2)‐like 2 activation‐induced hepatic very‐low‐density lipoprotein receptor overexpression in response to oxidative stress contributes to alcoholic liver disease in mice. Issue 4 (25th February 2014) - Wang, Zhigang; Dou, Xiaobing; Li, Songtao; Zhang, Ximei; Sun, Xinguo; Zhou, Zhanxiang; Song, Zhenyuan
<x xml:space="preserve">Abstract</x> Chronic alcohol consumption leads to hypertriglyceridemia, which is positively associated with alcoholic liver disease (ALD). However, whether and how it contributes to the development of fatty liver and liver injury are largely unknown. In this study we demonstrate that chronic alcohol exposure differently regulates the expression of very‐low‐density lipoprotein receptor (VLDLR) in adipose tissue and the liver. Whereas adipose tissue VLDLR is significantly down‐regulated, its hepatic expression is dramatically increased after chronic alcohol feeding. While HepG2 cells stably overexpressing VLDLR manifests increased intracellular triglyceride accumulation, VLDLR‐deficient mice are protective against fatty liver and liver injury after chronic alcohol exposure. Mechanistic investigations using both in vitro and in vivo systems reveal that oxidative stress‐induced nuclear factor (erythroid‐derived 2)‐like 2 (Nrf2) activation plays a critical role in alcohol‐induced VLDLR up‐regulation in hepatocytes, but not in adipocytes. Oxidative stress enhances VLDLR gene expression and protein abundance in primary hepatocytes, concomitant with the Nrf2 activation. Conversely, Nrf2 gene silencing abrogates oxidative stress‐induced VLDLR up‐regulation in the liver, but not in adipose tissue. In mice, alcohol exposure induces hepatic oxidative stress and Nrf2 activation. Supplementation of N‐acetylcysteine alleviates fatty liver and liver injury induced by chronic alcohol exposure, which is associated with suppressed Nrf2 activation and attenuated VLDLR increase in the liver. Furthermore, in comparison to wild‐type counterparts, Nrf2‐deficient mice demonstrate attenuated hepatic VLDLR expression increase in response to chronic alcohol exposure. Conclusion: Chronic alcohol consumption differently alters VLDLR expression in adipose tissue and the liver. Oxidative stress‐induced Nrf2 activation is mechanistically involved in VLDLR overexpression in hepatocytes in response to chronic alcohol consumption. Hepatic VLDLR overexpression plays an important role in the pathogenesis of ALD. (Hepatology 2014;59:1381‐1392)